2019
DOI: 10.5603/kp.a2018.0212
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of below-the-knee arterial blood flow after endovascular revascularisation of peripheral arteries as a potential predictor of clinical outcomes during one-year follow-up

Abstract: Background: Patients with advanced lower limb ischaemia are, at present, mainly treated using revascularisation. Aim: The aim of the study was to investigate whether the dynamics of blood flow in below-the-knee (BTK) arteries assessed by angiography correlate with clinical outcomes after a 12-month follow-up in patients with severe leg ischaemia treated percutaneously. Methods: The current study enrolled 287 consecutive patients who underwent 302 endovascular procedures on the infrainguinal arteries. The mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(30 reference statements)
0
0
0
Order By: Relevance
“…Yamaguchi T et al [26] also found an impact of runoff on the atherosclerotic burden in the femoropopliteal region, observing more ulcerated plaques in patients with poor runoff. Interestingly, Kaczmarczyk et al [27] found a negative correlation between the blood flow velocity and the treatment outcome of endovascular procedures conducted on the infrainguinal arteries. This finding stemmed from the observation that patients with only one patent artery had higher blood flow velocity, whereas in patients with more than one patent artery, the velocity was comparatively lower due to distribution of the blood among patent vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Yamaguchi T et al [26] also found an impact of runoff on the atherosclerotic burden in the femoropopliteal region, observing more ulcerated plaques in patients with poor runoff. Interestingly, Kaczmarczyk et al [27] found a negative correlation between the blood flow velocity and the treatment outcome of endovascular procedures conducted on the infrainguinal arteries. This finding stemmed from the observation that patients with only one patent artery had higher blood flow velocity, whereas in patients with more than one patent artery, the velocity was comparatively lower due to distribution of the blood among patent vessels.…”
Section: Discussionmentioning
confidence: 99%